Cesarean section and vaginal delivery in women with previous cesarean section: comparing maternal and neonatal outcomes - Sáenz, Claudia (2015)
Objectives: To determine maternal and perinatal outcomes in a new cesarean procedure and vaginal delivery in women with prior cesarean delivery. Design: Descriptive, series of cases study. Setting: Obstetrics Service, Hospital Nacional Cayetano Heredia, Lima, Peru. Participants: We included 1 591 patients who had prior cesarean delivery between January 1, 2001 and December 31, 2009. We used the Perinatal Information System, clinical charts and Blood Unit registry. Main outcome measures: Maternal and neonatal complications associated with cesarean section. Results: The rate of vaginal deliveries and cesarean deliveries in women with prior cesarean delivery were respectively 19% and 81%. We found 18 endometritis cases and 3 infections of the operative wound in the group of cesarean deliveries, and two endometritis and no infections in the vaginal birth group. There were few cases of low Apgar and no neonatal death. Conclusions: The percentage of maternal and neonatal complications was similar in both groups.